Essential Roles of the Linker Sequence Between Tetratricopeptide Repeat Motifs of Ethylene Overproduction 1 in Ethylene Biosynthesis - An, Chuanjing; Gao, Yuefang (Frontiers in Plant Science, 2021)
Ethylene influences root growth, gravitropism, and differentiation. Ethylene Overproduction 1 (ETO1) is a negative regulator in the ethylene biosynthesis process. However, the regulation mechanism of ETO1 remain largely unclear. In the present study, a novel eto1 allele (eto1-16) was isolated with typical triple phenotypes due to an amino acid substitution of G480C in the uncharacterized linker sequence between the TPR1 and TPR2 motif. Genetic and biochemical experiments further confirmed the eto1-16 mutation site. Sequence analysis revealed that G480 is conserved not only in two paralogs, EOL1 and EOL2, in Arabidopsis, but also in the homologous protein in other species. The glycine mutations (eto1-11, eto1-12, and eto1-16) did not influence their mRNA abundance, which is also reflected by mRNA secondary structures similar to those of the WT. The abnormal root phenotype of eto1-16 was caused by the disruption of the interaction with type 2 ACSs proteins. According to protein-protein interaction analysis, the balance of ETO1 and ACS5 pool is disturbed in eto1-16. Overall, the data suggest that the linker sequence between TPR motif and the glycine in TPR motifs is essential for ETO1 to bind with disparate downstream mediators.